2009
DOI: 10.1097/mao.0b013e31818d1cba
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cochlear Implantation on Vestibular Function

Abstract: Objective Determine the risk posed by cochlear implantation (CI) to the labyrinth. Study Design Prospective cohort study. Setting Academic tertiary referral center. Patients Thirty-six ears belonging to 35 adult CI candidates (mean: 46, range: 23–69 years old). Intervention Cochlear implantation. Main Outcome Measures Vestibular function was assessed using the quantitative 3D head impulse test (qHIT), clinical head impulse test (cHIT), post-headshake nystagmus (HSN), caloric electronystagmography (EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 43 publications
10
63
1
Order By: Relevance
“…This could be due to a bilateral impairment of vestibular receptors even when this was not always clearly reflected in the results of our neurootological test battery. This is in line with Melvin [7] and Enticott [5] whose data also show a poor correlation between the postoperative, subjective rating of vertigo and objective neurootological findings. It should be considered that the utricular maculae were not tested and could have been potentially impaired as well [22].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This could be due to a bilateral impairment of vestibular receptors even when this was not always clearly reflected in the results of our neurootological test battery. This is in line with Melvin [7] and Enticott [5] whose data also show a poor correlation between the postoperative, subjective rating of vertigo and objective neurootological findings. It should be considered that the utricular maculae were not tested and could have been potentially impaired as well [22].…”
Section: Discussionsupporting
confidence: 73%
“…In general, complications in cochlear implantation are rare nowadays because the procedure has been standardized to minimize any patient's risk. Specific surgical complications (apart from inflammation and bleeding) reported in the literature include an electrode dislocation, facial nerve lesion, but also dizziness and taste disorders [4][5][6][7][8]. The latter potential risks of vestibular and/or taste impairment have to be carefully discussed with the patients when a bilateral implantation is considered.…”
Section: Introductionmentioning
confidence: 97%
“…The data of oVEMPs after CI have not been reported yet. The rate of postoperative hypofunction was reported to be 13-86% in cVEMP (Todt et al, 2008;Krause et al, 2009;Licameli et al, 2009;Melvin et al, 2009;Krause et al, 2010;Wagner et al, 2010). Jin et al (2006)reported a response rate change in children with severe sensorineural hearing loss: seven of 12 patients presented normal cVEMPs before CI, but all disappeared after CI.…”
Section: Discussionmentioning
confidence: 95%
“…Todt et al (2008) found a 62.9% response rate of the cVEMP in 39 patients preoperatively, but 13 (21.0%) patients lost their normal responses of cVEMP postoperatively. Melvin et al (2009) reported a deterioration of cVEMP in five of 16 ears (31%) after CI. A cVEMP disappearance rate of 20% after surgery was found by Licameli et al (2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation